2020
DOI: 10.56536/ijmres.v10i1.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soft TQM Practices on Job Satisfaction and Organizational Commitment of Healthcare Professionals

Abstract: This study aims to measure the effect of soft TQM practices on job satisfaction and organizational commitment of healthcare professionals. Data were collected from three ISO 9000:2008 certified hospitals located in two northern cities of Pakistan. Out of 800 self-administered questionnaires distributed to doctors and nurses, 530 filled questionnaires were returned. Results were drawn by applying reliability, correlation, and linear regression analyses. Study proves that soft TQM practices exert a positive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Management and Business Research. (Ali et al, 2020) Effect of soft TQM practices on job satisfaction and organizational…”
Section: Citationsmentioning
confidence: 99%
“…Management and Business Research. (Ali et al, 2020) Effect of soft TQM practices on job satisfaction and organizational…”
Section: Citationsmentioning
confidence: 99%
“…In this vein, Khan et al, (2019) have found that TQM practices positively influenced employee job satisfaction, which in turn positively influenced employee creativity and proactive behaviors. In addition, Ali et al, 2020 have claimed that TQM practices positively influenced employee job satisfaction, organizational commitment, and employee performance. Moreover, Ababneh (2021) has affirmed that TQM practices positively influenced employee job satisfaction and employee engagement, which in turn positively influenced employee performance.…”
Section: Introductionmentioning
confidence: 99%